2017
DOI: 10.1080/21681376.2017.1286231
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of regional electricity demand for Turkey

Abstract: electricity sectors have experienced a transformation towards more liberalized and decentralized structure since the 1980s. this transformation process increases the importance of regional-level analysis. this study analyses the factors affecting regional electricity demand. as a case study, analysis is performed for turkey by employing a dynamic spatial lag panel data model. the model allows for the inclusion of spatial interaction effects into the analysis which are important but mostly ignored in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…Etkili Faktörler ortalamasının 0.15 olduğu ve birkaç uç değer haricinde 0-0.30 aralığında değiştiğini göstermektedir (Akarsu, 2017;Arısoy & Öztürk, 2014;Deryugina vd., 2017;Dilaver & Hunt, 2011;Erdoğdu, 2007;Halıcıoğlu, 2007;Ito, 2014;Madlaner vd., 2011). Tüketicilerin kısa dönemde daha fazla olmak üzere fiyat değişimine karşı duyarsız oldukları ve elektriğin zaruri bir ürün olduğu, bu çalışmaların ortak sonucudur.…”
Section: Kısa Vadedeunclassified
“…Etkili Faktörler ortalamasının 0.15 olduğu ve birkaç uç değer haricinde 0-0.30 aralığında değiştiğini göstermektedir (Akarsu, 2017;Arısoy & Öztürk, 2014;Deryugina vd., 2017;Dilaver & Hunt, 2011;Erdoğdu, 2007;Halıcıoğlu, 2007;Ito, 2014;Madlaner vd., 2011). Tüketicilerin kısa dönemde daha fazla olmak üzere fiyat değişimine karşı duyarsız oldukları ve elektriğin zaruri bir ürün olduğu, bu çalışmaların ortak sonucudur.…”
Section: Kısa Vadedeunclassified
“…The monthly electricity supply from conventional and renewable resources is modelled in another study using a seasonal autoregressive integrated moving average (SARIMA) model for the 2001-2020 period and it is shown that the SARIMA model successfully models the electricity supply data (Kurt et al, 2022). In another work, the regional electricity demand of Türkiye is investigated in the period of 1986-2013 using autoregressive integrated moving average model and it is shown that the utilized model has the root mean square error of 0.11 (Akarsu, 2017). Grey forecasting methods with rolling mechanism is utilized in another study for the modelling of the electrical energy demand forecasting of Türkiye for the 2015-2030 period where it is shown that nonhomogeneous Grey model with rolling mechanism increases the forecasting accuracy (Kusakci and Ayvaz, 2015).…”
Section: Literature Analysismentioning
confidence: 99%
“…The authors find spatial effects in Spanish residential electricity consumption. Akarsu (2017) analyses spatial interdependencies among different Turkish regions resulting from socio-economic relations, such as relocation of economic activity or migration, and spillover effects of policy measures by using a spatial panel data model. His findings show that energy policy related to only one province can affect electricity consumption in other provinces.…”
Section: Literaturementioning
confidence: 99%